Touchstone : Teacher's edition - McCarthy, Michael; McCarten, Jeanne; Helen Sandiford; Aldcorn, Sue; Battiste, Janet K.; Gitrzy, Andrew; Stafford-Yilmaz, Lynn (New York, U.S.A. : Cambridge University Press, 2010)
Touchstone is a groundbreaking new series that offers a fresh approach to teaching and learning North American English.
Contents TOMO 1 Introduction Teaching notes Unit 1: All about you Unit 2: In class Unit 3: Favorite people Unit 4: Every life Unit 5: Free time Unit 6: Neighborhoods Unit 7: Out and about Unit 8: Shopping Unit 9: A wide world Unit 10: Busy lives Unit 11: Looking back Unit 12: Fabulous food Selft-study listening Homework ideas Language summaries Testing program Student´s book audio scripts Workbook answer key TOMO 2 Introduction Teaching notes Unit 1: Making friends Unit 2: Interests Unit 3: Health Unit 4: Celebrations Unit 5: Growing un Unit 6: Around town Unit 7: Going away Unit 8: At home Unit 9: Things happen Unit 10: Communication Unit 11: Appearances Unit 12: Looking ahead Self-study listening Homework ideas Language summaries Testing program Student´s book audio scripts Workbook answer key
Incluye Contents
Keywords: ENGLISH -- GRAMMAR; INGLÉS -- GRAMÁTICA; ENGLISH -- TEACHING; ENGLISH -- STRATEGIES; INGLÉS CONVERSACIONAL -- INGLES - ESTRATEGIAS DE ENSEÑANZA -- INGLES - SPEAKING -- LEARNING ESTATEGIES